Hubungan antara Efikasi Diri Dengan Prokrastinasi Akademik pada Siswa SMK di Sijunjung - Fitri, Wenni; Rinaldi, Rinaldi (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
This study aims to determine the relationship between self-efficacy and procrastination academic in students at SMK in Sijunjung. This research uses quantitative methods with quantitative correlational research designs. The population in this study were high school students in Sijunjung with 100 students. The sampling technique used was purposive sampling. Where sampling is based on predetermined criteria by researchers. The Data collection tool using scale of self-efficacy and procrastination academic. Data analysis using product moment correlation coefficient. The results showed a positive relationship between self-efficacy and procrastination academic instudents at SMK in Sijunjung (r = 0.239; p =0.017